The Effect of Nearpod Interactive Media on Learning Motivation of Law Department Students in the Indonesian Language Course - Risnawati; Maulidina, St. Nur; Fransisca, Rosalia (Proceeding International Conference on Education, 2024)
This study examines the effectiveness of utilizing Nearpod as an interactive learning media in increasing student learning motivation. The research method used is a quantitative method with a pre-experimental design approach. The population of the study were law students who took Indonesian language courses, with a sample of 36 first-semester law students selected using purposive sampling techniques. Data collection techniques include observation, questionnaires, and documentation to obtain relevant data. The results of the study indicate that the use of Nearpod as an interactive learning media significantly increases student learning motivation. This increase in motivation occurs through the use of interesting Nearpod features such as videos, slide shows, interactive games, and time-based activities such as "Time to Climb" and "Fill in the Blank." In addition, this media is able to provide a more enjoyable learning experience and make students more involved in the learning process. Data analysis shows a significant difference before and after the implementation of Nearpod, which strengthens the conclusion that this media is effective in increasing learning motivation. The implication of this study is that Nearpod can be used as an alternative innovative learning media to encourage active student participation in class. This research also provides an important contribution to the development of technology-based learning media in the digital era. Integration of technology in education is a strategic step to increase the effectiveness of teaching in the digital era.